Impact of an inpatient nurse-initiated penicillin allergy delabeling questionnaire - Hilary Bediako; Lauren Dutcher; Aditi Rao; Kristen Sigafus; Christina Harker; Keith W. Hamilton; Olajumoke Fadugba (Cambridge University Press, 2022)
Penicillin allergy delabeling is an important component of antimicrobial stewardship and improves patient outcomes. We demonstrated the successful use of a nurse-initiated questionnaire to remove inappropriate penicillin allergy labels in inpatients. Nurses can play a key role in improving antibiotic allergy assessment and more broadly in interprofessional antimicrobial stewardship.